Pollination management in horticultural crops under protected conditions: a review (Current Horticulture, 2024)
Pollination is an essential process for almost all crops and plants, playing a vital role in ensuring a successful crop yield with  improved quality of fruits, seed and produce. For several years, honeybees have been the primary pollinators in most agricultural  systems under open field conditions, including greenhouses and net houses up to some extent. Honeybees, especially Apis  mellifera and Apis cerana indica are highly effective pollinators in natural environments, where they are able to freely forage and  access flowers. However, they may not be efficient pollinators under closed environmental conditions such as greenhouses and  net houses. In large areas, honeybees have shown reluctance to work under protected structures, and this has led to a decline  in pollination efficacy under these environments and conditions. As a result, research on the use of alternative pollinators  like bumblebees, carpenter bees, stingless bees, syrphid flies, etc. has been conducted under different structures. Henceforth  pollination management under greenhouses and net houses using alternative pollinators, have been discussed.
Keywords: Pollination management; horticultural; protected conditions